Integration of handcrafted and deep neural features for Melanoma classification - Rahman, Mohammad Saminoor; Hossain, Md. Jubayer; Islam, Siful; Kabir, Md. Nafiul; Sujon, Md. Kamrul Hasan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.